2018
DOI: 10.1021/acs.molpharmaceut.8b00359
|View full text |Cite
|
Sign up to set email alerts
|

An Indole–Chalcone Inhibits Multidrug-Resistant Cancer Cell Growth by Targeting Microtubules

Abstract: Multidrug resistance and toxic side effects are the major challenges in cancer treatment with microtubule-targeting agents (MTAs), and thus, there is an urgent clinical need for new therapies. Chalcone, a common simple scaffold found in many natural products, is widely used as a privileged structure in medicinal chemistry. We have previously validated tubulin as the anticancer target for chalcone derivatives. In this study, an α-methyl-substituted indole-chalcone (FC77) was synthesized and found to exhibit an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…Furthermore, antiproliferative/antitumor activities of chalcones have also been intensively studied [9][10][11][12][13][14]. The available studies revealed multitargeted activity of chalcones including various kinases [15], microtubules [16], multidrug-resistance proteins [17], or different signalling pathways associated with…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, antiproliferative/antitumor activities of chalcones have also been intensively studied [9][10][11][12][13][14]. The available studies revealed multitargeted activity of chalcones including various kinases [15], microtubules [16], multidrug-resistance proteins [17], or different signalling pathways associated with…”
Section: Introductionmentioning
confidence: 99%
“…Cong et al reported an indole-chalcone derivative (FC77, Scheme 6) that can arrest cancer cell growth by binding to tubulin, exhibiting a similar mechanism of action as colchicine. FC77 exhibited a potent growth inhibitor of a majority of NCI-60 human cancer cell lines with GI50 ~ 6 μM [79]. The ability of FC77 to retain its cytotoxicity against multi-drug resistant cancer cell lines (with nanomolar GI values) and low cytotoxicity levels towards normal mobilized peripheral blood cells revealed that FC77 may be a potential therapeutic agent in treating multi-drug resistant cancers such as NSCLC.…”
Section: Tubulin Inhibitionmentioning
confidence: 99%
“…The ability of FC77 to retain its cytotoxicity against multi-drug resistant cancer cell lines (with nanomolar GI values) and low cytotoxicity levels towards normal mobilized peripheral blood cells revealed that FC77 may be a potential therapeutic agent in treating multi-drug resistant cancers such as NSCLC. Moreover, the direct interaction of FC77 with tubulin and inhibition of microtubule dynamics with IC50 values of 3 nM compared to popular drugs such as paclitaxel and vincristine with IC50 values of 14 nM and 37 nM, respectively, makes it an attractive microtubule-targeting agent for the treatment of multidrug-resistant cancers [79]. The synthesis of FC77 was accomplished in a single step, as shown in Scheme 6 [79].…”
Section: Tubulin Inhibitionmentioning
confidence: 99%
See 2 more Smart Citations